Cephalometric measurements: comparison between analog X-Ray film and digital cephalometric image - Md. Lani, Ruzaini; Setan, Halim; Chong, Albert K.; Majid, Zulkepli (2006)
This research is focused on the comparison of measurements between analog x-ray film and digital cephalometric image. This study is designed to determine the best measurement method between manually tracing and using computer software. Two (2) types of data from the same patient were used in this research. The data is analog x-ray film and digital cephalometric image (obtained from scanned x-ray film). A total of ten landmarks were used for comparison. All landmarks on the film and digital cephalometric image were traced using manual method (via tracing paper) and computerized method (via Rhinoceros 2.0 software) respectively. The landmarks were identified five times for each method to ensure the precision of the landmark identification. The results of landmark identification for both manual and computerize methods were compared by measurement of angle SNA, SNB, ANB and MMPA, and linear distance between Po-Or, PNS-ANS and Go-Me. This comparison gives the value of mean and standard deviation to show the best measurement method between manual and computerized approaches.